2017
DOI: 10.18186/journal-of-thermal-engineering.338907
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Numerical Simulation of Turbulent Forced Convection in a Rectangular Pipe Provided With Waved Porous Baffles

Abstract: Numerical simulations of flow and heat transfer in a serpentine heat exchanger configuration are presented to demonstrate application of porous media techniques in heat exchanger analyses. In this study, steady-state 3D turbulent forced convection flow and heat transfer characteristics in a rectangular pipe with baffles attached inside pipe have been numerically investigated under constant wall heat flux boundary condition. Numerical study has been carried out for Reynolds number of 20000-50,000, Prandtl numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The macroscopic transport equations for the turbulent kinetic energy and dissipation rate in the porous medium are as follow [28,30]:…”
Section: Governing Equations In Porous Regionmentioning
confidence: 99%
“…The macroscopic transport equations for the turbulent kinetic energy and dissipation rate in the porous medium are as follow [28,30]:…”
Section: Governing Equations In Porous Regionmentioning
confidence: 99%
“…Porous mediums which are constructed with high thermal conductivity materials like metal foams can increase the fluid-solid contact which results in enhancing the heat transfer [2][3][4]. In recent years, Using of porous fins to enhance the performance of thermal systems like photovoltaic-thermal (PVT) systems, high power semiconductor devices, electronic cooling systems, heat exchangers, enhancing of the heat transfer of fluids in enclosures, pipes and channels, thermal insulators etc, [5][6][7][8][9][10][11][12] has been an attractive subject for many researchers. Kiwan and Al-Namir [1] employed finite element method to analyze the enhancing performance of porous fins compared to solid fins and demonstrated that in the large Darcy numbers, the effect of the Rayleigh number is more significant.…”
Section: Introductionmentioning
confidence: 99%